A comparison of patient education practices and perceptions of novice and experienced physiotherapists in Australian physiotherapy settings. (April 2017) - Forbes, Roma; Mandrusiak, Allison; Smith, Michelle; Russell, Trevor
Abstract: Background: Patient education is an integral component of physiotherapy practice. Little is known about the differences in reported use and perception of patient education between experienced and novice physiotherapists. Understanding these differences has important implications for training approaches and physiotherapy practice. Objectives: To compare how experienced and novice physiotherapists report frequency of patient education practices and their perceptions of the importance of these practices. Design and methods: A web-based purpose-designed survey was developed, piloted and administered to practicing physiotherapists through direct email. Of 305 complete responses, two subgroups were explored for comparative analysis: 'novice' (≤5years' experience, n = 52); and 'experienced' (≥11 years' experience, n = 204). Results: The experienced group rated 14 of 15 educational items higher than the novice group in relation to frequency of use and perceived importance. Experienced physiotherapists reported a significantly higher frequency of using one-to-one discussion, personalised handouts and explicitly seeking patient understanding (p < 0.05). Novice physiotherapists perceived more barriers to patient education, particularly those related to characteristics of the patient (p < 0.05). Conclusion: Experienced physiotherapists report higher use of self-management education and education content that is patient-centred. Experienced therapists report a higher frequency of seeking explicit patient understanding to evaluate their teaching than novice physiotherapists and perceive fewer patient-related barriers to their practice. These findings are important when considering teaching and learning of patient education skills. Students or novice physiotherapists may benefit from strategies to facilitate patient-centred education, self-management education, evaluation approaches and strategies to manage barriers. Highlights: Experienced physiotherapists report higher use of self-management education. Experienced physiotherapists report higher use of patient-centred content. Experienced physiotherapists report higher use of seeking patient understanding. Experienced physiotherapists perceive fewer barriers to patient education.